Usage behavior and health benefit perception of youth in urban parks: A case study from Qingdao, China - Wenfei Yao; Jiayue Yun; Yiping Zhang; Tian Meng; Zhiyue Mu (Frontiers Media S.A., 2022)
With the development of the urban park, people's cognition of the relationship between the environment and public health has been improved, and higher requirements for the living environment have been put forward. As an important group of park users, youths often have different needs regarding the health benefits brought by urban parks. To explore the potential relationship among youth's satisfaction with urban parks, their usage behavior, and health benefit perception, this article presents some constructive suggestions for the development of healthy landscapes in urban parks. Researchers have selected five typical urban parks from different areas in Qingdao, China. Furthermore, we have used the survey method by combining the practices of "issuing questionnaires, observing and interviewing" with the goal of collecting data on 500 park visitors in autumn, including information on social demography, the satisfaction of park landscape variables, and usage behavior and health perception. A linear regression model has been used to analyze the correlation among "landscape variables," "usage behavior," and "health benefit perception." Results have shown that urban green landscapes and waterscapes can significantly affect youth's social health perception and static behavior. Moreover, static behaviors such as relaxation have a great impact on mental health perception. The results of this study will be beneficial in understanding youth's needs for landscapes when using urban parks. In addition, it will provide insight for the urban planners and landscape designers to design urban parks from the perspective of youth.